Prevention of Dental Biofilm Formation with Polyphenols: A Systematic Review - Schestakow, Anton; Meyer-Probst, Clara Theres; Hannig, Christian; Hannig, Matthias (Planta Medica, 2022)
Polyphenols are plant secondary products with health-promoting properties against various degenerative or infectious diseases, and thus may help in the prevention of oral diseases. The aim of the present systematic review was to investigate polyphenols as a possible adjuvant in inhibiting dental biofilm formation, which is an important precondition for the most prevalent oral disease – caries and periodontitis. A literature search was conducted using the databases PubMed, CENTRAL and Scopus. Only studies with oral healthy participants and plaque level as outcome were included. Data search and extraction was conducted by two authors independently. Of the 211 initially identified studies, only six met all inclusion criteria. Meta-analysis was performed with five studies using the random effect model. Treatment with polyphenols reduced the plaque level in comparison to a negative control, but not significantly. Strong evidence of heterogeneity was observed. The diversity and complexity of polyphenols and their preparation need to be considered. There is no clear evidence that clinical use of polyphenols can prevent dental biofilm formation. Additional research with more and larger randomized controlled trials are required.
Keywords: polyphenols; dental plaque; preventive dentistry; medicinal plants